Space, time, and sustainability: The status and future of life cycle assessment frameworks for novel biorefinery systems. (May 2022) - Vance, C.; Sweeney, J.; Murphy, F.
Abstract: For stakeholders and decision makers within the bioeconomy, it is important that sustainability assessment methodologies be holistic, reliable, and accurate. Life cycle assessment (LCA) methodologies are well-known for their ability to avoid burden shifting by considering the impacts of a product, process, or system throughout the full life cycle. However, when it comes to assessing advanced multifunctional systems within the bioeconomy i.e. biorefineries, methodological challenges arise. Such issues are discussed at length in this review paper, which include the goal, scope, and allocation methods, land use considerations, handling of biogenic carbon and emissions, impacts assessed, simplification of feedstocks and processes, regionality, and future foreground and background systems. Furthermore, the review discusses challenges in capturing social and economic impacts with LCA methodologies, with social assessments lacking data and appropriate quantitative indicators and economic assessments lacking diversity in stakeholder and cost inclusivity. Finally, this review confirms the importance of temporal factors, regional differences, and integrating multidimensional approaches to sustainability analysis, highlighting developing LCA methodologies which successfully address these areas. Methodologies to address spatial considerations include exergetic LCIA, natural capital assessment, and integration of supply chain modelling, while methodologies to address dynamic variability include process modelling integration, system dynamics modelling integration, agent-based modelling integration, consequential LCA, prospective LCA, and dynamic LCIA. Finally, extended LCC, extended LCIA, and MCDA can address challenges identified in multidimensional sustainability integration. Highlights: Biorefineries are part of a circular bioeconomy but should be critically assessed. LCA can be used but must overcome methodological challenges. Main challenges involve consideration of space, time, and overall sustainability. Spatial and temporal issues can be addressed through systems modelling integration. Social and economic aspects can be integrated through LCSA methodologies.